P30-27 A non-animal safety assessment framework for systemic, reproductive and developmental toxicity - M. Dent; S. Cable; P. Carmichael; P. Kukic; S. Malcomber; I. Muller; A. Punt; G. Reynolds; J. Reynolds; S. Scott; A. White; K. Wolton; et al. (Toxicology Letters, 2025)

Characterizing juvenile blacktip shark ( Carcharhinus limbatus ) nursery areas in the Galapagos: new methods and understandings - Lauren S. Goodman; Yasuní Chiriboga‐Paredes; Jaye E. Cable; Alex Hearn (Journal of Fish Biology, 2025)
New approaches to abundance surveying utilizing unoccupied aerial vehicles (UAVs) are proving to be effective tools in marine and terrestrial environments. We explored UAV efficacy for surveys in the Galapagos Marine Reserve (GMR), where relative abundance patterns of juvenile sharks and subsequent classifications of putative nursery areas based on environmental drivers are lacking. The UAV method allowed greater temporal and spatial coverage. We expanded classification of shark nursery habitat through monthly drone surveys and environmental data collection at 14 sites around San Cristobal Island (GMR) from November 2018 to July 2019. In the period of surveying, 56 flights identified 453 juvenile Carcharhinus limbatus (blacktip shark). Classification of nurseries followed three criteria, necessitating higher density, short‐term residency, and annual site fidelity in target locations. We developed preliminary generalized linear models to elucidate potential environmental parameters influencing the perceived abundance and habitat preference of juveniles. Four sites were identified as either potential nurseries or nursery areas for the target species based on previous excursions. An averaged model was subsequently created from the models found to best explain deviance patterns ( R 2 = 0.10–0.44) in perceived shark abundance and habitat preference. Relative variable importance (RVI) values further clarified the parameters most associated with higher juvenile presence. This approach provides a systematic method of abundance surveying while simultaneously beginning the process of defining when and where we expect to find higher abundance through environmental modelling of most influential parameters to perceived abundance in this environment.

Rare earth element assessment in Jezero crater using the Planetary Instrument for X-ray Lithochemistry on the Mars 2020 rover Perseverance: A case study of cerium - S.J. VanBommel; S. Sharma; T.V. Kizovski; C.M. Heirwegh; J.R. Christian; A.L. Knight; B. Ganly; A.C. Allwood; J.A. Hurowitz; M.M. Tice; M.L. Cable; W.T. Elam; et al. (Icarus, 2025)

P19-67 Using Next Generation Risk Assessment (NGRA) to make safety decisions for cosmetic ingredients under regulatory scrutiny - A. White; S. Cable; M.T. Baltazar; M. Dent; N. Hewitt; H. Li; J. Reynolds; S. Spriggs (Toxicology Letters, 2024)

P19-11 Establishing scientific confidence in a NAM toolbox and workflow using a flexible framework - M.T. Baltazar; G. Reynolds; M. Dent; P.L. Carmichael; P. Kukic; S. Malcomber; A. Middleton; K. Przybylak; A. Punt; J. Reynolds; S. Scottt; A. White; et al. (Toxicology Letters, 2024)

P01-01 A review of in silico and in vitro methods for use in a risk assessment of a substance acting via oestrogen or androgen modalities - K. Roylance; R. Brown; G. Panter; O. Tran; O. Green; A. Riu; A. Giusti; A. Loisy; C. Choi; D. Bury; D. Lange; J. Naciff; et al. (Toxicology Letters, 2024)

OS02-02 Establishing scientific confidence in physiologically based kinetic (PBK) models for quantitative in vitro-to-in vivo extrapolations (QIVIVE) in the absence of in vivo kinetic data - A. Punt; M.T. Baltazar; B. Nicol; S. Cable; N.J. Hewitt; M.P. Dent; H. Li (Toxicology Letters, 2024)

OS01-08 Assessing the protectiveness and utility of a new approach methodology-based toolbox for systemic toxicity - M. Dent; M. Baltazar; S. Cable; P. Carmichael; S. Hatherell; P. Kukic; S. Malcomber; A. Middleton; A. Punt; G. Reynolds; J. Reynolds; S. Scott; et al. (Toxicology Letters, 2024)

S10-01 Making safety decisions for a sunscreen active ingredient using next-generation risk assessment: benzophenone-4 case study - M.T. Baltazar; S. Cable; A. Punt; N.J. Hewitt; B. Nicol; P. Kukic; S. Scottt; S. Malcomber; R. Mascarenhas; C. Alexander-White; J. Reynolds; J. Houghton; et al. (Toxicology Letters, 2024)

P25-01: Evaluating New Approach Methodologies for use in Next Generation Risk Assessment - S. Cable; M. Baltazar; J. Reynolds; M. Dent; H. Li; A. Middleton (Toxicology Letters, 2023)

Geochemical and physical variability of Icelandic tephra fields and glaciovolcanic sandur to inform spatial sampling in Mars biosignature searches - Morgan L. Cable; Alexander M. Sessa; Erika Rader; Anna C. Simpson; Ashley M. Hanna; Diana M. Gentry; Scot M. Sutton; Elena S. Amador; Carlie Novak; Chloe LeCates; Mark Helmlinger; Amanda M. Stockton; et al. (Planetary and Space Science, 2023)

Functional immunogenetic variation, rather than local adaptation, predicts ectoparasite infection intensity in a model fish species - Karl P. Phillips; Joanne Cable; Ryan S. Mohammed; Sebastian Chmielewski; Karolina J. Przesmycka; Cock van Oosterhout; Jacek Radwan (Molecular Ecology, 2021)
Natural host populations differ in their susceptibility to infection by parasites, and these intrapopulation differences are still an incompletely understood component of host‐parasite dynamics. In this study, we used controlled infection experiments with wild‐caught guppies ( Poecilia reticulata ) and their ectoparasite Gyrodactylus turnbulli to investigate the roles of local adaptation and host genetic composition (immunogenetic and neutral) in explaining differences in susceptibility to infection. We found differences between our four study host populations that were consistent between two parasite source populations, with no indication of local adaptation by either host or parasite at two tested spatial scales. Greater values of host population genetic variability metrics broadly aligned with lower population mean infection intensity, with the best alignments associated with major histocompatibility complex (MHC) “supertypes”. Controlling for intrapopulation differences and potential inbreeding variance, we found a significant negative relationship between individual‐level functional MHC variability and infection: fish carrying more MHC supertypes experienced infections of lower severity, with limited evidence for supertype‐specific effects. We conclude that population‐level differences in host infection susceptibility probably reflect variation in parasite selective pressure and/or host evolutionary potential, underpinned by functional immunogenetic variation.

Expansion of frozen hybrids in the guppy ectoparasite, Gyrodactylus turnbulli - Mateusz Konczal; Karolina J. Przesmycka; Ryan S. Mohammed; Christoph Hahn; Jo Cable; Jacek Radwan (Molecular Ecology, 2021)
Hybridization is one of the major factors contributing to the emergence of highly successful parasites. Hybrid vigour can play an important role in this process, but subsequent rounds of recombination in the hybrid population may dilute its effects. Increased fitness of hybrids can, however, be frozen by asexual reproduction. Here, we identify invasion of a ‘frozen hybrid’ genotype in natural populations of Gyrodactylus turnbulli , a facultatively sexual ectoparasitic flatworm that causes significant damage to its fish host. We resequenced genomes of these parasites infecting guppies from six Trinidad and Tobago populations, and found surprisingly high discrepancy in genome‐wide nucleotide diversity between islands. The elevated heterozygosity on Tobago is maintained by predominantly clonal reproduction of hybrids formed from two diverged genomes. Hybridization has been followed by spread of the hybrids across the island, implying a selective advantage compared with native genotypes. Our results thus highlight that a single outcrossing event may be independently sufficient to cause pathogen expansion.

Gene duplications, divergence and recombination shape adaptive evolution of the fish ectoparasite Gyrodactylus bullatarudis - Mateusz Konczal; Karolina J. Przesmycka; Ryan S. Mohammed; Karl P. Phillips; Francisco Camara; Sebastian Chmielewski; Christoph Hahn; Roderic Guigo; Jo Cable; Jacek Radwan (Molecular Ecology, 2020)
Determining the molecular basis of parasite adaptation to its host is an important component in understanding host–parasite coevolution and the epidemiology of parasitic infections. Here, we investigate short‐ and long‐term adaptive evolution in the eukaryotic parasite Gyrodactylus bullatarudis infecting Caribbean guppies ( Poecilia reticulata ), by comparing the reference genome of Tobagonian G. bullatarudis with other Platyhelminthes, and by analysing resequenced samples from local Trinidadian populations. At the macroevolutionary timescale, we observed duplication of G‐protein and serine proteases genes, which are probably important in host–parasite arms races. Serine protease also showed strong evidence of ongoing, diversifying selection at the microevolutionary timescale. Furthermore, our analyses revealed that a hybridization event, involving two divergent genomes, followed by recombination has dramatically affected the genetic composition of Trinidadian populations. The recombinant genotypes invaded Trinidad and replaced local parasites in all populations. We localized more than 300 genes in regions fixed in local populations for variants of different origin, possibly due to diversifying selection pressure from local host populations. In addition, around 70 genes were localized in regions identified as heterozygous in some, but not all, individuals. This pattern is consistent with a very recent spread of recombinant parasites. Overall, our results are consistent with the idea that recombination between divergent genomes can result in particularly successful parasites.

Long-term cleaning patterns of the sharknose goby (Elacatinus evelynae) - Katie Dunkley; Amy R. Ellison; Ryan S. Mohammed; Cock van Oosterhout; Kathryn E. Whittey; Sarah E. Perkins; Jo Cable (Coral Reefs, 2019)

Higher habitual dietary caffeine consumption is related to lower experimental pain sensitivity in a community-based sample - Demario S. Overstreet; Terence M. Penn; Sarah T. Cable; Edwin N. Aroke; Burel R. Goodin (Psychopharmacology, 2018)

Getting into hot water: sick guppies frequent warmer thermal conditions - Ryan S. Mohammed; Michael Reynolds; Joanna James; Chris Williams; Azad Mohammed; Adesh Ramsubhag; Cock van Oosterhout; Jo Cable (Oecologia, 2016)

Relationship between European eel Anguilla anguilla infection with non‐native parasites and swimming behaviour on encountering accelerating flow - L. R. Newbold; F. A. Hockley; C. F. Williams; J. Cable; A. J. Reading; N. Auchterlonie; P. S. Kemp (Journal of Fish Biology, 2015)
The effect of Anguillicola crassus , Pseudodactylogyrus bini and Pseudodactylogyrus anguillae infection on the behaviour of downstream migrating adult European eels Anguilla anguilla as they encountered accelerating water velocity, common at engineered structures where flow is constricted ( e.g . weirs and bypass systems), was evaluated in an experimental flume. The probability of reacting to, and rejecting, the velocity gradient was positively related to A. crassus larval, adult and total abundance. High abundance of Pseudodactylogyrus spp. reduced this effect, but A. crassus was the strongest parasitic factor associated with fish behaviour, and abundance was positively related to delay in downstream passage. Delayed downstream migration at hydraulic gradients associated with riverine anthropogenic structures could result in additional energetic expenditure for migrating A. anguilla already challenged by A. crassus infection.

Parasites of Trinidadian guppies: evidence for sex‐ and age‐specific trait‐mediated indirect effects of predators - Jessica F. Stephenson; Cock van Oosterhout; Ryan S. Mohammed; Joanne Cable (Ecology, 2015)
Predation pressure can alter the morphology, physiology, life history, and behavior of prey; each of these in turn can change how surviving prey interact with parasites. These trait‐mediated indirect effects may change in direction or intensity during growth or, in sexually dimorphic species, between the sexes. The Trinidadian guppy, Poecilia reticulata presents a unique opportunity to examine these interactions; its behavioral ecology has been intensively studied in wild populations with well‐characterized predator faunas. Predation pressure is known to have driven the evolution of many guppy traits; for example, in high‐predation sites, females (but not males) tend to shoal, and this anti‐predator behavior facilitates parasite transmission. To test for evidence of predator‐driven differences in infection in natural populations, we collected 4715 guppies from 62 sites across Trinidad between 2003 and 2009 and screened them for ectosymbionts, including Gyrodactylus . A novel model‐averaging analysis revealed that females were more likely to be infected with Gyrodactylus parasites than males, but only in populations with both high predation pressure and high infection prevalence. We propose that the difference in shoaling tendency between the sexes could explain the observed difference in infection prevalence between males and females in high‐predation sites. The infection rate of juveniles did not vary with predation regime, probably because juveniles face constant predation pressure from conspecific adults and therefore tend to shoal in both high‐ and low‐predation sites. This represents the first evidence for age‐ and sex‐specific trait‐mediated indirect effects of predators on the probability of infection in their prey.

Empirical Trials of Plant Field Guides - W. D. HAWTHORNE; S. CABLE; C. A. M. MARSHALL (Conservation Biology, 2014)
We designed 3 image‐based field guides to tropical forest plant species in Ghana, Grenada, and Cameroon and tested them with 1095 local residents and 20 botanists in the United Kingdom. We compared users’ identification accuracy with different image formats, including drawings, specimen photos, living plant photos, and paintings. We compared users’ accuracy with the guides to their accuracy with only their prior knowledge of the flora. We asked respondents to score each format for usability, beauty, and how much they would pay for it. Prior knowledge of plant names was generally low ( Pruebas Empíricas de Guías de Campo de Plantas Hawthorne, Cable & Marshall

The effect of acute simulated moderate altitude on power, performance and pacing strategies in well-trained cyclists - Sally A. Clark; P. C. Bourdon; W. Schmidt; B. Singh; G. Cable; K. J. Onus; S. M. Woolford; T. Stanef; C. J. Gore; R. J. Aughey (European Journal of Applied Physiology, 2007)

The Guppy as a Conservation Model: Implications of Parasitism and Inbreeding for Reintroduction Success - COCK VAN OOSTERHOUT; ALAN M. SMITH; BERND HÄNFLING; INDAR W. RAMNARINE; RYAN S. MOHAMMED; JOANNE CABLE (Conservation Biology, 2007)
Ex situ conservation is of increasing importance to prevent the extinction of endangered animals in the wild. Despite low success rates of reintroduction programs few researchers have investigated empirically the efficacy of captive breeding regimes for the release of captive‐bred vertebrates. We used guppies ( Poecilia reticulata ) from two populations in Trinidad to compare different conservation breeding regimes. The upper Aripo population was chosen for its small effective population size ( N e ≈ 100) and genetic isolation, which makes it representative of many endangered natural populations. By contrast, the lower Aripo population is a genetically diverse, much larger population ( N e ≈ 2400). We examined three captive‐breeding regimes: (1) inbreeding fish crossed with their full siblings, (2) minimized inbreeding, no consanguineous matings, and (3) control fish crossed at random. We kept pedigree records for all regimes so that we could calculate inbreeding coefficients over four generations. The body size and fertility of guppies was significantly reduced due to inbreeding depression. The genetic load of sterile equivalents was particularly high for the lower Aripo population. Body size also declined due to breeding conditions in the captive environment. After four generations in captivity, the fish were released into a mesocosm in Trinidad. Captive‐bred guppies were extremely susceptible to gyrodactylid parasites (58% survival rate) compared with their wild counterparts (96% survival). A reduced level of immunogenetic variation due to inbreeding and lack of exposure to natural parasites may have rendered captive‐bred individuals more prone to infectious disease. The threat of disease outbreak is particularly high when naive captive‐bred hosts are released in wild populations. Susceptible, captive‐bred hosts could facilitate the transmission of parasites throughout the wild population, thus initiating an epidemic. This risk could potentially be reduced by prior exposure to parasites before release and gradual release of captive‐bred individuals.

Polychlorinated Biphenyls and Chlordane in the Gonads of Paddlefish, Polyodon spathula, from the Ohio River - D. T. Gundersen; M. D. Krahling; J. J. Donosky; R. G. Cable; S. D. Mims (Bulletin of Environmental Contamination and Toxicology, 1998)

Mechanism of induction of heme oxygenase by metalloporphyrins in primary chick embryo liver cells: Evidence against a stress-mediated response - Edward E. Cable; Otto S. Gildemeister; Joyce A. Pepe; Richard W. Lambrecht; Herbert L. Bonkovsky (Molecular and Cellular Biochemistry, 1997)